MY EXPERIENCE IN PRICE-LEVEL ADJUSTMENT. - Sih, S. T. (The Accounting Review, 1955)
Abstract In the article, the author shares his views on price level adjustments. The problems with pricing, and financial statements is discussed. According to the author, the application of price indices is limited by two conditions, the speed of inflation or deflation, and the differentiation between a general price index and individual commodity price indices. In China, a series of changes of currencies, Fapi, Golden Yuan Notes, Taiwan Dollars, etc. create much problem. By statutes, not only the assets and liabilities, but the capital is also required to be revalued. Chinese communists had applied rice prices to the revaluation of assets and liabilities before they occupied mainland China. Afterwards the price index was compiled and applied. The Government moved from the mainland to this island in 1949, and a currency reform was effected in June for the purpose of strengthening national powers. By statute, current assets and liabilities were converted into the new currency on a fixed rate, and fixed assets and capital revalued at the end of that year.